Willingness to Communicate (WTC) in Arabic Among Students at a State Islamic University - Muhammad Nur Kholis; Burhan Yusuf Habibi; Muhammad Zaenuri; Luthfi Qoriatul Hasanah (ALSINATUNA, 2023)
Willingness to Communicate (WTC) plays a crucial role in second language acquisition, significantly influencing both the frequency and fluency of language use across different contexts. This study examines the levels of WTC among students in the Arabic Language Education (PBA) and Arabic Language and Literature (BSA) programs at UIN Raden Mas Said Surakarta, Central Java, Indonesia, within three communicative settings: in-class (IC), out-of-class (OC), and digital contexts (DC). The research further investigates the underlying psychological and contextual factors that shape students’ WTC in Arabic. Utilizing a mixed-methods approach, quantitative data were collected from 213 participants  and analyzed using descriptive statistics, while qualitative insights were derived from focus group discussions. Results reveal that BSA students consistently demonstrate higher WTC across all contexts, particularly in classroom interactions. Contributing factors include the learning environment, perceived language competence, and psychological variables such as anxiety and self-confidence. The study underscores the importance of supportive pedagogical environments and participatory teaching strategies in enhancing students’ communicative motivation. By identifying both enabling and inhibiting factors, this research contributes to Arabic language education discourse by advocating for context-sensitive interventions that foster communicative competence and sustain language use in diverse academic and social settings.